2020
DOI: 10.3389/fpsyg.2020.00527
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Insomnia Subtypes in Relation to Demographic Characteristics, Anxiety, Depression, Alcohol Consumption and Use of Hypnotics

Abstract: The aim of the present study was to examine the prevalence of insomnia subtypes in relation to several demographic characteristics, as well as to investigate the prevalence of possible anxiety and depression, alcohol consumption and use of hypnotics within the different insomnia subtypes. Methods:The present study was based on an extensive web-based survey made publicly available in 2012. The data was downloaded in January 2019, after 113 887 people had responded to parts of, or the entire questionnaire. The 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 47 publications
8
50
1
1
Order By: Relevance
“…This is in line with the view that symptoms in all phases of the sleep period (i.e., difficulty initiating sleep, trouble maintaining sleep, and early morning awakenings) are the most severe insomnia subtype, 30 influencing daily functioning such as energy and mood. 9 , 30 Our finding has important clinical implications, suggesting that reducing the severity of insomnia symptoms in people with chronic insomnia could be an important strategy towards the prevention of chronic pain and pain-related disability. However, further investigations are needed to establish whether it is the number of nighttime symptoms per se that impose an increased risk or if these associations are modified by certain combinations of nighttime symptoms.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This is in line with the view that symptoms in all phases of the sleep period (i.e., difficulty initiating sleep, trouble maintaining sleep, and early morning awakenings) are the most severe insomnia subtype, 30 influencing daily functioning such as energy and mood. 9 , 30 Our finding has important clinical implications, suggesting that reducing the severity of insomnia symptoms in people with chronic insomnia could be an important strategy towards the prevention of chronic pain and pain-related disability. However, further investigations are needed to establish whether it is the number of nighttime symptoms per se that impose an increased risk or if these associations are modified by certain combinations of nighttime symptoms.…”
Section: Discussionmentioning
confidence: 78%
“…Although speculative, it is possible that poor sleep maintenance is the most troublesome symptom when it comes to pain, 15 , 16 , 36 and that problems with initiating sleep and/or early awakening are related to other characteristics such as age, gender and comorbid conditions (eg, mental health, use of hypnotics). 9 However, further investigations are required to disentangle whether the development of chronic and disabling pain depends on the specific type and duration of the nighttime symptoms. So far, the processes linking insomnia and chronic musculoskeletal pain may be conceptualized through a framework of interconnected processes including immune responses, neurobiological changes, and altered cognitive and emotional pain processing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insomnia subtypes may also be based on consistency (persistent, remission, relapse) ( Wu et al, 2014 ). In clinical practice, the most commonly used subdivision is related to when in the main sleep period (at sleep onset, during the sleep period, or in the morning) the insomnia symptoms occur ( Yokoyama et al, 2010 ; Bjoroy et al, 2020 ). In a recent population-based study with more than 60,000 participants, it was shown that the symptoms of anxiety and depression, and hypnotic use, were higher among participants with insomnia consisting of a combination of sleep onset, sleep maintenance, and early morning awakening problems as compared to participants with other insomnia subtypes (e.g., insomnia with pure sleep onset or sleep maintenance problems) ( Bjoroy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%